Diazoxide is a powerful cardioprotectant but is not feasible in a realistic infarct scenario - Kleinbongard, Petra; Lieder, Helmut; Skyschally, Andreas; Heusch, Gerd (Frontiers in Cardiovascular Medicine, 2023)
Introduction Diazoxide is a powerful cardioprotective agent that activates mitochondrial ATP-dependent K-channels and stimulates mitochondrial respiration. Diazoxide reduced infarct size in isolated rodent heart preparations and upon pretreatment in juvenile pigs with coronary occlusion/reperfusion. We aimed to study the use of diazoxide in a more realistic adult pig model of reperfused acute myocardial infarction when diazoxide was administered just before reperfusion. Methods and results In a first approach, we pretreated anaesthetised adult Göttingen minipigs with 7 mg kg−1 diazoxide (n = 5) or placebo (n = 5) intravenously over 10 min and subjected them to 60 min coronary occlusion and 180 min reperfusion; blood pressure was maintained by use of an aortic snare. The primary endpoint was infarct size (triphenyl tetrazolium chloride staining) as a fraction of area at risk; no-reflow area (thioflavin-S staining) was the secondary endpoint. In a second approach, diazoxide (n = 5) was given from 50 to 60 min coronary occlusion, and blood pressure was not maintained. There was a significant reduction in infarct size (22% ± 11% of area at risk with diazoxide pretreatment vs. 47% ± 11% with placebo) and area of no-reflow (14% ± 14% of infarct size with diazoxide pretreatment vs. 46% ± 20% with placebo). With diazoxide from 50 to 60 min coronary occlusion, however, there was marked hypotension, and infarct size (44% ± 7%) and area of no-reflow were not reduced (35% ± 25%). Conclusions Cardioprotection by diazoxide pretreatment was confirmed in adult pigs with reperfused acute myocardial infarction but is not feasible when diazoxide is administered in a more realistic scenario before reperfusion and causes hypotension.